Moore's Laws of Wages - Taussig, F. W.; Moore, Henry L. (Quarterly Journal of Economics, 1912)
Journal Article Moore's Laws of Wages Get access F. W. Taussig F. W. Taussig Harvard University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 26, Issue 3, May 1912, Pages 511–518, https://doi.org/10.2307/1883534 Published: 01 May 1912